Complementation of contact tracing by mass testing for successful containment of beta COVID-19 variant (SARS-CoV-2 VOC B.1.351) epidemic in Hong Kong - Vincent Chi-Chung Cheng; Gilman Kit-Hang Siu; Shuk-Ching Wong; Albert Ka-Wing Au; Cecilia Suk-Fun Ng; Hong Chen; Xin Li; Lam-Kwong Lee; Jake Siu-Lun Leung; Kelvin Keru Lu; Hazel Wing-Hei Lo; Evelyn Yin-Kwan Wong; et al. (Elsevier, 2021)
Background: Global dissemination of SARS-CoV-2 Variants of Concern (VOCs) remains a concern. The aim of this study is to describe how mass testing and phylogenetic analysis successfully prevented local transmission of SARS-CoV-2 VOC in a densely populated city with low herd immunity for COVID-19. Methods: In this descriptive study, we conducted contact tracing, quarantine, and mass testing of the potentially exposed contacts with the index case. Epidemiological investigation and phylogeographic analysis were performed. Findings: Among 11,818 laboratory confirmed cases of COVID-19 diagnosed till 13th May 2021 in Hong Kong, SARS-CoV-2 VOCs were found in 271 (2.3%) cases. Except for 10 locally acquired secondary cases, all SARS-CoV-2 VOCs were imported or acquired in quarantine hotels. The index case of this SARS-CoV-2 VOC B.1.351 epidemic, an inbound traveler with asymptomatic infection, was diagnosed 9 days after completing 21 days of quarantine. Contact tracing of 163 contacts in household, hotel, and residential building only revealed 1 (0.6%) secondary case. A symptomatic foreign domestic helper (FDH) without apparent epidemiological link but infected by virus with identical genome sequence was subsequently confirmed. Mass testing of 0.34 million FDHs identified two more cases which were phylogenetically linked. A total of 10 secondary cases were identified that were related to two household gatherings. The clinical attack rate of household close contact was significantly higher than non-household exposure during quarantine (7/25, 28% vs 0/2051, 0%; p<0.001). Interpretation: The rising epidemic of SARS-CoV-2 VOC transmission could be successfully controlled by contact tracing, quarantine, and rapid genome sequencing complemented by mass testing. Funding: Health and Medical Research Fund Commissioned Research on Control of Infectious Disease (see acknowledgments for full list).